PENETAPAN GARIS BATAS ZONA EKONOMI EKSKLUSIF INDONESIA DAN INDIA DALAM PENEGAKAN KEDAULATAN TERITORIAL DITINJAU DARI HUKUM INTERNASIONAL - Rivai H Sihaloho; Suhaidi Suhaidi; Arif Arif (Journal of USU International Law, 2014)
ABSTRACT Sovereignty of a country occured in three- dimensional force areas, namely land, sea and air is restricted by international law and the sovereignty of other countries. But often there is no apparent limit to the area of ​​the country, especially in marine areas that pose the question of sovereignty. To uphold the sovereignty and laws of a country in the sea area needed a complete maritime delimitation and conducted under the provisions of the International Law of the Sea, which is set in the UN Convention on the Law of the Sea (UNCLOS 1982). However, in determining the maritime boundary, the Convention on the Law of the Sea 1982 needs to be studied carefully to see that large contribution to the issue of maritime boundaries. This thesis is motivated by not doing EEZ delimitation between Indonesia and India, where the border is located between Rondo island in Aceh and Nicobar islands in India. Maritime boundary of the continental shelf which is located at coordinate points specified in the Indian Ocean and Andaman Sea, has been agreed by the two countries. But problems still arise between the two countries because of frequent violations of territory by both parties, especially the illegal fishing that done by the fishermen which can disrupt diplomatic relations between the two countries. This thesis uses normative research methods. The nature of the research in this thesis is a descriptive study, and data collection techniques used are literature studies. The qualitative analysis is done using data that has been obtained through the study of literature and then analyzed and qualified in order to get an answer from the formulation of the problem Delimitation of the exclusive economic zones of Indonesia and India are urgently required given the enormous potential of Indonesian waters in that zone and to avoid bigger problems. Also remember to make such determination would affect the territorial integrity of Indonesia. In an effort determination of the exclusive economic zones of Indonesia and the Indian government can hold back approval through peaceful negotiations on the basis of international law by using the principle of equal distance (equidistant) to achieve a fair way out unless there are special circumstances that should be considered so as not to harm the national interests of both countries. Keywords: Exclusive Economic Zones, Territorial Sovereignty